1981
DOI: 10.1111/j.1365-2559.1981.tb01788.x
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate mucin production in gall bladder metaplasia and neoplasia–an immunohistological study

Abstract: This study demonstrates the presence of three antigens in glandular metaplasia occurring in patients with cholecystitis and cholelithiasis: specifically carcinoembryonic antigen (CEA), large intestinal mucin antigen (LIMA) and small intestinal mucin antigen (SIMA). These antigens could not be detected in normal gall bladder mucosa or in squamous metaplasia of the gall bladder. The occurrence of the three intestine-associated antigens in three carcinomas was irregular. In one mucinous carcinoma, only SIMA could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1983
1983
1999
1999

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The frequency of metaplastic epithelium in diseased, nontumorous gallbladders is high, 72.8%, according to LAITIO (17). Several authors have found antral-type metaplasia in association with gallbladder carcinoma in man (3,10,16,22) and 2 mucinous carcinomas were bordered by antral-type mucosa (16). Mucinous metaplasia has therefore been considered a possible premalignant condition.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of metaplastic epithelium in diseased, nontumorous gallbladders is high, 72.8%, according to LAITIO (17). Several authors have found antral-type metaplasia in association with gallbladder carcinoma in man (3,10,16,22) and 2 mucinous carcinomas were bordered by antral-type mucosa (16). Mucinous metaplasia has therefore been considered a possible premalignant condition.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor cells had to be neutral mucin-positive, N-acetylsialomucin-positive, sulphomucin-negative, O-acetylsialomucin-negative, and CEA-positive, where distribution of the antigens was glandular, (i.e., the antigens were present within a lumen of the gland-like structure) or apical (i.e., the antigens were dispersed along the luminal surface of cells in the gland-like structure) [9][10][11][12][13]. A pattern was classified as a well-differentiated adenocarcinoma (G1) if it was composed of well-formed small glands similar to those in normal mucosa.…”
Section: Materials and Methods Materialsmentioning
confidence: 99%
“…To construct relatively homogenous groups of gallbladder adenocarcinomas, a number of tumors previously enrolled in the data bank as well-differentiated adenocarcinomas (G1) or moderately differentiated adenocarcinomas (G2) were carefully reexamined. Tumor cells had to be neutral mucin-positive, N-acetylsialomucin-positive, sulphomucin-negative, O-acetylsialomucin-negative, and CEA-positive, where distribution of the antigens was glandular, (i.e., the antigens were present within a lumen of the gland-like structure) or apical (i.e., the antigens were dispersed along the luminal surface of cells in the gland-like structure) [9][10][11][12][13]. A pattern was classified as a well-differentiated adenocarcinoma (G1) if it was composed of well-formed small glands similar to those in normal mucosa.…”
Section: Materials and Methods Materialsmentioning
confidence: 99%